EVALUASI RUANG TERBUKA HIJAU PADA TAMAN KOTA WADUK PLUIT, JAKARTA UTARA - Daniel Andrea; Priyendiswara Agustina Bella (Jurusan Arsitektur dan Perencanaan, 2023)
City parks are a type of public green open space that play an important role in improving the quality of the urban environment. There are several aspects needed for an urban park, namely ecological, social, and economic. Ecological function will be evaluated by comparing the existing conditions with standard ecological criteria. The social function is evaluated from the activity of the park and the results of the questionnaire. The economy is evaluated from the regulations set by DPMPTSP. The results of temperature measurements at Pluit Reservoir City Park can be reduced to 2.7ºC. The humidity control function can increase humidity up to 7.8%. The noise control function can be reduced to 10.5 dBA . In the windbreak function, based on the results of the assessment based on the KPI, it is in a good category. Based on the results of the analysis of visitor activity, the majority of visitors who visited the Pluit Reservoir City Park were from North Jakarta with the most age group being 21-25 years whose activities were mostly sitting, jogging, and leisurely walking. In the analysis of physical conditions that are included in the top priority or quadrant 1 (Important but not as expected) are park benches, trash cans, and garden lights. As for other things, such as pavements that are still not in accordance with the standards of Ministerial Regulation No. 30 of 2006. Based on the results of the economic analysis, this park can be used for commercial activities such as events, competitions, bazaars, weddings, etc. So that this park can reap revenue starting from IDR 1,250,000 / location to IDR 2,500,000 / location. Keywords: City park; ecological function; economic function; social function Abstrak Taman kota merupakan salah satu jenis ruang terbuka hijau publik berperan penting dalam meningkatkan kualitas lingkungan perkotaan. Terdapat beberapa aspek yang diperlukan untuk sebuah taman kota yaitu ekologi, sosial, dan ekonomi. Fungsi ekologis akan dievaluasi dengan membandingkan kondisi eksisting dengan kriteria standar ekologi. Pada fungsi sosial dievaluasi dari aktivitas taman dan hasil kuesioner. Pada ekonomi dievaluasi dari peraturan yang diatur DPMPTSP. Hasil pengukuran suhu Taman Kota Waduk Pluit dapat direduksi hingga 2,7ºC. Pada fungsi pengontrol Kelembaban dapat meningkatkan kelembaban hingga 7,8%. Pada fungsi pengontrol kebisingan dapat direduksi hingga 10,5 dBA . Pada fungsi penahan angin, berdasarkan dari hasil penilaian berdasarkan KPI, adalah berkategori baik. Pada hasil analisis aktivitas pengunjung, mayoritas pengunjung yang berkunjung ke Taman Kota Waduk Pluit adalah dari Jakarta Utara dengan kelompok usia paling banyak adalah 21 – 25 tahun yang beraktivitas mayoritas adalah duduk – duduk, jogging, dan jalan santai. Pada analisis kondisi fisik yang masuk ke dalam prioritas utama atau kuadran 1 (Penting tetapi belum sesuai harapan) adalah bangku taman, tempat sampah, dan lampu taman. Adapun hal lainnya seperti perkerasan yang masih belum sesuai dengan standar Peraturan Menteri No.30 Tahun 2006. Pada hasil analisis perekonomian, taman ini dapat digunakan dalam kegiatan komersil seperti event, perlombaan, bazaar, pernikahan, dll. Sehingga taman ini dapat meraup pendapatan dimulai dari Rp1.250.000,-/lokasi hingga Rp2.500.000/ lokasi. Kata Kunci: Taman Kota, fungsi ekologis, fungsi sosial, fungsi perekonomian.